Efektivitas Samsak Digital sebagai Alat Inovatif dalam Pengukuran dan Peningkatan Kekuatan Tendangan Taekwondo - Kurniawan, Edi; Supriyatnak, Kokom; Jumesam, Jumesam (Jurnal Porkes, 2024)
This study aims to assess the effectiveness of a digital punching bag as an innovative tool to measure and improve dolyo chagi kick power. This study used a quasi-experimental design with a pretest posttest control group design. The population of this study was 60 taekwondo athletes aged 12-16 years. The sampling technique was carried out by purposive sampling. The research tools and instruments included a digital punching bag, which was designed with a pressure sensor to measure kick strength. The results of statistical analysis showed a significant increase in kicking power in the experimental group, with an average increase of 17.11 points compared to 1.34 points in the control group. Statistical tests (t = 15.198; p < 0.05) confirmed the effectiveness of the digital punching bag in significantly increasing kicking power. Descriptive statistics, the mean pretest score of the experimental group was 153.29, with scores of 145 to 168, and increased to 170.40 in the posttest, with scores of 157 to 187. The control group showed only minimal improvement, from an average pretest of 147.23 (range 143-156) to 148.57 on the posttest (range 145-157). The study concluded that the digital punching bag is an innovative and effective tool for improving athlete performance through accurate measurement and real-time feedback.